Histochemical and Immunohistochemical Analysis of the Stomach of Rhinella icterica (Anura, Bufonidae). (10th November 2014) - Machado-Santos, Clarice; Pelli-Martins, Adriana Alves; Abidu-Figueiredo, Marcelo; de Brito-Gitirana, Lycia
Abstract : The stomach of Rhinella icterica was analyzed at light microscopy, employing histochemical techniques, lectin histochemistry, and immunohistochemistry for identifying enteroendocrine cells (EC). Although the stomach was composed of fundic and pyloric regions, its wall is formed by mucosa, submucosa, muscularis, and serosa. The mucosa was lined by a simple columnar mucous epithelium, supported by loose connective tissue. Several tubular, simple glands were composed of mucous neck cells, containing oxynticopeptic cells and EC cells. The mucous neck cells were rich in neutral glycoconjugates. The oxynticopeptic cells were predominant in fundic glands, exhibiting weaker alcianophilic reaction at their apical cytoplasm. Serotonin (5-HT) immunoreactive (IR) cells occurred throughout the entire stomach, preferentially located among mucous cells at upper part of the fundic glands. The muscularis mucosae, formed of smooth muscle, separated the mucosal layer from the submucosa, both of which were constituted by loose connective tissue, but without glands. Lymphoid modules occurred in the mucosa at the boundary at the stomach and the gut. In addition, the muscularis was constituted by two sublayers, the circular internal and the longitudinal external, being recovered by the connective tissue of the serosa.